Dzień gdańskiej parafii Bożego Ciała. (Gdańsk : [s.n.], 1947)
Afisz inf. o uroczystościach 8.06.1947 r.
Keywords: Kościoły -- Polska -- Gdańsk -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- życie religijne